ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA PERBANDINGAN - Rosi Oktavia; Masta Hutajulu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to identify and describe the results of the errors that students experience in the process of solving problems of comparative story problems. The researchers applies a qualitative descriptive methods when conducting his research. The subjects of this study were students of class VII-A of SMP Negeri 8 Cimahi, a total of 24 students. The data collection technique used has three stages: (a) data reduction, (b) data presentation, (c) drawing conclusions and using help tables in order to determine the percentage level of error. The instrument used is in the form of a description of 5 test questions. The results of student work were analyzed based on the Newman procedure. Based on the results of the study, the highest percentage of errors was found in the average process skill error, which was 33.3%, while the lowest error was found in the average percentage of reading errors, which was 5.8%.